Ergebnisse der Forschungsreise E. Möhn 1956 nach El Salvador - Nr. 9 Gallmücken (Diptera, Itonididae) aus El Salvador. 7. Teil: Lasiopteridi. - Möhn, Edwin (Contributions to Entomology = Beiträge zur Entomologie, 1964)
The present, 7th part of the "Gallmücken (Diptera, Itonididae) aus El Salvador" includes the description of 4 new genera, 1 new subgenus and 14 new species, all of them of the supertribus Lasiopteridi. The species Neolasioptera erigerontis (Felt), hitherto known only from North America, has been demonstrated to occurr in the neotropical region. Nomenclatural Acts trilobata Möhn, 1964 (Alycaulus), spec. n. gilibertiae Möhn, 1964 (Brachylasioptera), spec. n. rotunda Möhn, 1964 (Brachylasioptera), spec. n. iresinis Möhn, 1964 (Epilasioptera), spec. n. eupatoriensis Möhn, 1964 (Isolasioptera), spec. n. Brachylasioptera Möhn, 1964 (Itonididae), gen. n. Epilasioptera Möhn, 1964 (Itonididae), gen. n. Isolasioptera Möhn, 1964 (Itonididae), gen. n. Lobolasioptera Möhn, 1964 (Itonididae), gen. n. media Möhn, 1964 (Lobolasioptera), spec. n. brickelliae Möhn, 1964 (Neolasioptera), spec. n. caleae Möhn, 1964 (Neolasioptera), spec. n. camarae Möhn, 1964 (Neolasioptera), spec. n. celtis Möhn, 1964 (Neolasioptera), spec. n. compositarum Möhn, 1964 (Neolasioptera), spec. n. dentata Möhn, 1964 (Neolasioptera), spec. n. Dilasioptera Möhn, 1964 (Neolasioptera), sgen. n. parvula Möhn, 1964 (Neolasioptera), spec. n. serrata Möhn, 1964 (Neolasioptera (Dilasioptera)), spec. n.